Liquid Metal Smart Materials toward Soft Robotics - Sen Chen; Hong-Zhang Wang; Tian-Ying Liu; Jing Liu (Advanced Intelligent Systems, 2023)
Unlike conventional rigid machines, soft robots generally have unique operation styles that rely heavily on soft matter engineering and smart material systems. Owing to the superior merits of both metals and fluids, liquid metal smart materials are increasingly being innovatively used as soft actuators and sensors to construct soft robots. To promote further development and prosperity in this field, this review organizes and summarizes the typical progress in liquid metal smart materials, with a special focus on their robotic response behaviors. In particular, the article emphasizes the concept of smart composite systems consisting of liquid metals and synergistic substances (e.g., solutions, particles, and polymers). The response behaviors of liquid metal smart materials under the actions of external factors (electricity, magnetism, ultrasound, light, heat, etc.) are examined and the smart properties occurring during these responses, such as motion, transformation, self‐organization, adaptive healing, and autonomous sensing, are identified. Furthermore, soft actuators, control systems, and robots based on liquid metal smart materials are summarized and elaborated upon. Finally, the potential directions worth pursuing and challenges are outlined. It is expected that this review will stimulate further investigations into liquid metal smart materials with the aim of building a new generation of soft robots.